Nutritional quality and adulterants of cow raw milk, pasteurized and cottage cheese collected along value chain from three regions of Ethiopia - Haftom Zebib; Dawit Abate; Ashagrie Zewdu Woldegiorgis (Heliyon, 2023)
Milk is a nutritionally rich food for humans. However, fulfilling the quality of milk is a major concern for milk factories, nutrient requirements, and public health. The objective of this research was to assess the composition of raw and pasteurized milk and cheese, evaluate change in milk and cheese composition along the value chain, and identify adulteration of milk. A total of 160 composite samples were determined using lactoscan and conventional approved methods along value chain. Results indicate that there were significant (p < 0.05) changes of in milk composition along the value chain in the study regions. The range values were; total solid (8.41–11.7%), protein (2.25–3.06%), fat (2.16–3.17%), lactose (3.33–4.76%), ash (0.52–0.73%), P (62.7–84.2 mg/100 g) and Ca (78.2–109 mg/100 g) of liquid milk were obtained in all regions. Liquid milk was found to be adulterated by water along the value chains in all regions (ranged from 0 to 24.8%). Formalin (4 samples) and starch (1 sample) were detected at farmer's and collectors' respectively. In all regions, there was no significant (p > 0.05) difference in cheese nutritional quality between farmers and retailers. The grand mean for moisture, protein, fat, total ash, Ca, P and pH values were 77.1%, 17.1%, 1.42%, 1.18%, 37.8 mg/100 g, 88.2 mg/100 g and 3.7 respectively. Comparison of liquid products with the Compulsory Ethiopian Standard (CES) indicates that 80.2% for fat, protein, and SNF in raw and pasteurized milk were below the CES. In conclusion, liquid milk had poor nutritional composition and varied along the value chain in the study regions. Moreover, there is milk fraud where all dairy value chain add water into milk and milk consumers are consuming lower nutrients and paying for substandard liquid milk. Therefore, training should be provided to all value chain to improve the quality of milk products and quantification of formalin and other adulterants need to be further studied.